2012
DOI: 10.1111/j.1365-2524.2012.01060.x
|View full text |Cite
|
Sign up to set email alerts
|

Shared care: the barriers encountered by community-based palliative care teams in Ontario, Canada

Abstract: To meet the complex needs of patients requiring palliative care and to deliver holistic end‐of‐life care to patients and their families, an interprofessional team approach is recommended. Expert palliative care teams work to improve the quality of life of patients and families through pain and symptom management, and psychosocial spiritual and bereavement support. By establishing shared care models in the community setting, teams support primary healthcare providers such as family physicians and community nurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
14
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 38 publications
3
14
0
1
Order By: Relevance
“…This “shared care” model of CBPPC can assume myriad forms but typically involves the PPC team in the role of consultant to a local provider (eg, local oncologist, community‐based PPC clinician, hospice agent, or primary pediatrician), with the local clinician acting as the driver of care . However, because the coordination and provision of CBPPC require a level of expertise and time commitment that may be beyond the scope or comfort of local providers, in certain circumstances, it may be preferable to use a model in which CBPPC clinicians directly manage and provide care, as opposed to lending expertise via consultation. The caveat, however, is that this CBPPC‐led model is not sustainable in the long term without adequate funding, resources, and staffing .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…This “shared care” model of CBPPC can assume myriad forms but typically involves the PPC team in the role of consultant to a local provider (eg, local oncologist, community‐based PPC clinician, hospice agent, or primary pediatrician), with the local clinician acting as the driver of care . However, because the coordination and provision of CBPPC require a level of expertise and time commitment that may be beyond the scope or comfort of local providers, in certain circumstances, it may be preferable to use a model in which CBPPC clinicians directly manage and provide care, as opposed to lending expertise via consultation. The caveat, however, is that this CBPPC‐led model is not sustainable in the long term without adequate funding, resources, and staffing .…”
Section: Introductionmentioning
confidence: 99%
“…However, because the coordination and provision of CBPPC require a level of expertise and time commitment that may be beyond the scope or comfort of local providers, in certain circumstances, it may be preferable to use a model in which CBPPC clinicians directly manage and provide care, as opposed to lending expertise via consultation. The caveat, however, is that this CBPPC‐led model is not sustainable in the long term without adequate funding, resources, and staffing . Lack of reimbursement from insurance companies, insufficient clinical personnel to manage large patient volumes, and inadequate ancillary support to track and process paperwork contribute to suboptimal access to CBPPC …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Shared care is established when the team works in consultation with family physicians and community nurses. In our previous research with the teams of concern herein, identified barriers, such as lack of funding for non-physician team members and the inability to secure buy-in from primary care providers, were shown to have posed challenges in their pursuit of the shared care model [15]. Additional research has also explored the factors or facilitators employed by the teams to overcome challenges, such as securing funding for non-physician team members, and undertaking capacity building initiatives with primary care providers [16].…”
Section: Introductionmentioning
confidence: 99%